SEE - Nirta, Caterina; Mandic, Danilo; Philippopoulos-Mihalopoulos, Andreas; Pavoni, Andrea (Law and the Senses, 2018)
"Vision traditionally occupies the height of the sensorial hierarchy. The sense of clarity and purity conveyed by vision, allows it to be explicitly associated with truth and knowledge. The law has always relied on vision and representation, from eye-witnesses to photography, to imagery and emblems. The law and its normative gaze can be understood as that which decrees what is permitted to be and become visible and what is not. Indeed, even if law's perspectival view is bound to be betrayed by the realities of perception, it is nonetheless productive of real effects on the world. This first title in the interdisciplinary series 'Law and the Senses' asks how we can develop new theoretical approaches to law and seeing that go beyond a simple critique of the legal pretension to truth. This volume aims to understand how law might see and unsee, and how in its turn is seen and unseen. It explores devices and practices of visibility, the evolution of iconology and iconography, and the relation between the gaze of the law and the blindness of justice. The contributions, all radically interdisciplinary, are drawn from photography, legal theory, philosophy, and poetry."